Effect of pulp tester probe placement site on the response of maxillary anterior teeth - Jalil Modaresi; Amir Reza Heshmat Mohajer; Hossein Aghili; Morteza Khorshidi; Faramarz Rostami Chavoshlo; Amirmohamad Mahabadi (Tehran University of Medical Sciences, 2012)
Background and Aims: Electric pulp testing is used for diagnosis of the pulp status. This test is technique sensitive and hence may elicit positive or negative false response in case of inaccurate use. The optimal site for placement of the probe tip has not been determined. The aim of this study was to evaluate the effect of pulp tester probe placement site on the response of maxillary teeth.Materials and Methods: A total of 378 teeth (126 central incisors, 126 lateral incisors and 126 canines) in 67 voluntary 20-35 year-old patients were selected. Three sites on each tooth (incisal edge, labial and lingual surfaces) were tested with an electrical pulp tester and responses were recorded. Data were analyzed by Repeated Measure ANOVA test.Results: The central teeth showed significantly lower sensation threshold than lateral and canine teeth (P<0.001). The incisal edge of tooth were significantly more sensitive compared to labial and lingual surfaces (P=0.008).Conclusion: This study showed that the optimum site for placement of pulp tester probe was incisal edge.